Understanding nature’s contributions to people in ancient biocultural systems through network and RLQ analysis - Andreea Nita; Kinga Olga Réti; Ruxandra Mălina Petrescu-Mag; Dacinia Crina Petrescu; Cristian Maloș; László Csákány; Dietmar Gross; Frank Wagener; Laurentiu Rozylowicz; Tibor Hartel (Ecosystems and People)
This research delves into the emerging paradigm of biocultural systems, focusing on the intricate social-ecological dynamics which created and maintained an ancient farming system, the European wood-pastures. Innovatively conceptualizing wood-pastures as biocultural systems, this study employs a network approach to unravel the complex interactions between human activities and the natural particularities within these environments. By using field surveys and interviews conducted in Transylvania, Romania, this research reconstructs the traditional social-ecological drivers behind the preservation of ancient wood-pastures and their Nature’s Contributions to People (NCP). It identifies key variables and their centrality within the biocultural network, emphasizing that the rich natural values of wood-pastures are inextricably linked to management features. We employ RLQ and fourth corner analyses to investigate the interconnections among biophysical context, biocultural features (i.e. human made and natural features), and NCP, revealing significant correlations and gradients between the broad biophysical setting and the wood-pasture NCP. The findings underscore the importance of maintaining traditional management practices and stewardship to conserve the biodiversity and cultural heritage of wood-pastures. We contribute to a deeper comprehension of biocultural systems and offer insights for effective management and governance of traditional farming landscapes in Europe and beyond.